Regional Climate Simulations With the Community Earth System Model. (10th June 2018) - Gettelman, A.; Callaghan, P.; Larson, V. E.; Zarzycki, C. M.; Bacmeister, J. T.; Lauritzen, P. H.; Bogenschutz, P. A.; Neale, R. B.
Abstract: The spectral element (SE) variable‐resolution (VR) mesh dynamical core is tested in developmental versions of the Community Earth System Model version 2 (CESM2). The SE dynamical core is tested in baroclinic wave, aquaplanet and full physics configurations to evaluate variable‐resolution simulations against uniform high and uniform low‐resolution simulations. Different physical parameterization suites are also evaluated to gauge their sensitivity to resolution. Dry dynamical core variable‐resolution cases compare well to high‐resolution tests. More recent versions of the atmospheric physics, including cloud schemes for CESM2, are less sensitive to changes in horizontal resolution. Most of the sensitivity is due to sensitivity to time step and interactions between deep convection and large‐scale condensation, which is expected from the closure methods. The resulting full physics SE‐VR model produces a similar climate to the global low‐resolution mesh and similar high‐frequency statistics in the high‐resolution region. The SE‐VR simulations are able to reproduce uniform high‐resolution results, making them an effective tool for regional climate simulations at lower computational cost. Some biases are reduced (orographic precipitation in Western United States), but biases do not necessarily go away at high resolution (e.g., summertime surface temperatures). Variable‐resolution grids are a viable alternative to traditional nesting for regional climate studies and are available in CESM2. Plain Language Summary: This manuscript describes comprehensive tests of a numerical climate model that has high horizontal resolution in one region. This enables high‐resolution simulations of climate, and extreme weather events that occur on small scales to be simulated at lower computational costs. Results indicate that the model represents low‐resolution climate well, and also reproduces extreme climate statistics in the region with high resolution. We conclude that the variable resolution model is a good way to simulate and predict regional climate. Key Points: Comprehensive tests of a variable resolution dynamical core are conducted Cloud schemes for CESM2 are not very sensitive to changes in horizontal resolution Variable‐resolution grids are a viable alternative to traditional nesting for regional climate studies and are available in CESM2